Karakteristik Fisikokimia Tepung Kecambah Kedelai - Astawan, Made; Hazmi, Khaidar (JURNAL PANGAN, 2016)
Soybean is a strategic commodity in Indonesia because it is one of the most important crops after rice and maize. Indonesian people like to consume processed soybean products due to several reasons, such as their relatively inexpensive price and highly nutritional content. One of the processes that can improve the quality of soy nutrition is germination process. In this study, comparative physicochemical characteristics of germinated soybean flour (TKK) and soybean flour (TK) is investigated. First, soybean and germinated soybean are dried using a freeze dryer, then their sizes are reduced using a blender and finally they are sieved using a 100 mesh sieve. TKK and TK products are analyzed based on not only their chemical and physical characteristics but also their functional properties. It is proven that germination process can improve the chemical characteristics of soybean flour, such as increasing the contents of ash, protein, and antioxidant capacity, but decreasing the fat content.  TKK is significantly higher than TK on bulk density. Protein functional characteristics of TKK are also better on foam capacity and emulsion capacity as compared to TK.